Effect of sonication on the synthesis of exfoliated polymer clay nanocomposites - Erciyes, A. T.; Bayram, Y.; Akyol, E. (SCIENTIFIC PUBL-INDIA, 2019)
Research efforts on polymer clay nanocomposites have been drawing a great deal of attention due to their great enhancement of properties in many areas. Here, we synthesized exfoliated polymer clay nanocomposites (PCNs) by in situ polymerization of oil based vinyl macromonomer with styrene in the presence of clay. In order to facilitate the clay dispersion mixing was carried out by sonication besides classical mixing. The polymer clay nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), X-ray diffraction spectroscopy (XRD) and thermal gravimetric analysis (TGA). The samples prepared by mixing in sonication bath gave lower char yield compared to the samples of classical mixing.
Keywords: Polymer clay nanocomposite; exfoliated; sonication; X-ray diffraction spectroscopy; thermal gravimetric analysis; POLYMER/LAYERED SILICATE NANOCOMPOSITES; IN-SITU SYNTHESIS; Chemistry